Symptomatic Type IV Dual Left Anterior Descending Coronary Artery - Kyriacos Papadopoulos MD (Journal of Investigative Medicine High Impact Case Reports, 2016)
Dual left anterior descending coronary artery is a rare congenital anomaly with 4 subtypes. Double left anterior descending coronary artery originating from the left main stem and the right coronary artery (type IV dual left anterior descending artery) has been reported to occur in 0.01% to 0.7% of patients undergoing cardiac catheterization. We report a case of a 49-year-old woman who was found to have this anomaly during coronary angiography. The patient had been complaining of chest pain that mimics angina pectoris and exercise tolerance test was positive for myocardial ischemia.